2005
DOI: 10.1017/s002211200500488x
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study of the influence of initial perturbations on the turbulent Rayleigh–Taylor instability

Abstract: The effect of initial conditions on the growth rate of turbulent Rayleigh-Taylor (RT) mixing has been studied using carefully formulated numerical simulations. A monotone integrated large-eddy simulation (MILES) using a finite-volume technique was employed to solve the three-dimensional incompressible Euler equations with numerical dissipation. The initial conditions were chosen to test the dependence of the RT growth coefficient (α b ) and the self-similar parameter (β b = λ b /h b ) on (i) the amplitude, (ii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
91
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(101 citation statements)
references
References 51 publications
10
91
0
Order By: Relevance
“…The influence of ICs on classical RT-unstable flows has received considerable attention in the literature [12,19,[38][39][40][41]. Previous studies [17,42] have identified two alternative phenomenological models that describe the convergence towards self-similarity (Eq.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The influence of ICs on classical RT-unstable flows has received considerable attention in the literature [12,19,[38][39][40][41]. Previous studies [17,42] have identified two alternative phenomenological models that describe the convergence towards self-similarity (Eq.…”
Section: Resultsmentioning
confidence: 99%
“…2) in the classical case of RTI with a broad-band multimode initial perturbation undergoing constant acceleration. The first such approach, known as bubble merger, considers that two or more bubbles may merge and form larger structures as a part of a continuous and repetitive process during the evolution of the mixing layer [17,19]. In contrast, bubble competition involves amplification and saturation of long wavelengths and they lead the flow.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations